Peran pendidikan anti korupsi dalam membentuk generasi berintegritas di era digital Indonesia - Asruro, Devi Maziyah (Maliki Interdisciplinary Journal, 2026)
Corruption remains a serious problem in Indonesia, with widespread impacts on the economic, social, and political sectors. Efforts to eradicate corruption are not limited to law enforcement alone; they also require a preventative approach through education. This study aims to analyze the role of anti-corruption education in shaping a generation with integrity in the digital era. The method used is a qualitative approach through literature review from various relevant scientific sources. The results show that anti-corruption education plays a crucial role in instilling the values ​​of honesty, responsibility, and transparency in the younger generation. However, its implementation still faces various obstacles, such as a lack of integration within the curriculum, theoretical learning methods, and a lack of role models in the surrounding environment. Therefore, innovations in learning, such as the use of digital technology and a contextual approach, are needed for greater effectiveness. With optimal implementation, anti-corruption education is expected to shape the character of a younger generation with integrity and contribute to creating a society free from corruption.